SISTEM INFORMASI DAPUR CERDAS UNTUK PEMBERITAHUAN DAN PENANGANAN TERHADAP KEBOCORAN GAS LPG BERBASIS MICROCONTROLER - Yul Hendra (Jurnal Sistem Informasi dan Informatika (Simika), 2018)
Liquid Petroleum Gas or well-known as LPG Gas is now a staple for every household in Indonesia, we often hear the explosion due to leakage from LPG gas cylinders in the room. Not a few casualties are falling as a result of LPG gas leak in this room. LPG gas that leaks in a closed room can be dangerous because the leaking gas cannot get out of the room, triggered either by matches, gas compost, gas is struck which causes a fire and even a great explosion. This is the background of this research, the author wants to make a prototype device that can prevent the occurrence of explosions or gas fires in the kitchen or a room. The method used in this study is a trial method, assembling microcontroller tools to enter program logic into it that can know that a gas leak has occurred. Not only that, after the device can detect that there has been a LPG gas leak in a room, then the device can also function as an anticipation of an explosion or fire, by automatically opening the kitchen or room window, by opening the room / kitchen window, then the gas will automatically exit the room and the fire and explosion will not occur. When a device detects a gas leak in the kitchen, the alarm will automatically sound as well as a tool to open the door as an automatic handling to avoid fire or explosion. So a series of processes and logic from this tool if applied in a kitchen or room will be able to become a system that works automatically in the detection, notifying, and anticipating the occurrence of fire or explosion due to LPG gas leak